2001
DOI: 10.1007/s001920170039
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Ureteral Obstruction during Complex Urogynecologic Surgery

Abstract: Intraoperative cystoscopy has been recommended to identify unsuspected bladder and ureteral injuries resulting from gynecologic surgery. We retrospectively reviewed 157 cases of complex urogynecologic procedures at our institution. Intraoperative cystoscopy revealed no bladder injuries. Five cases of unsuspected ureteral obstruction were identified (3.2%). One case of ureteral ligation was diagnosed and repaired intraoperatively. The remaining 4 cases were found to represent chronic ureteral obstruction result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…A retrospective review concluded that preoperative evaluation may be useful in selected cases, but it was also admitted that preoperative measures have not resulted in a reduction in intraoperative injuries. 15 The only risk factor for injury was blood loss greater than 800 mL and increased operating time. Degree of difficulty (determined by the resident performing the case) was not significant, but unexplained is the increased injury rate with increased body mass index and increased uterine size ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective review concluded that preoperative evaluation may be useful in selected cases, but it was also admitted that preoperative measures have not resulted in a reduction in intraoperative injuries. 15 The only risk factor for injury was blood loss greater than 800 mL and increased operating time. Degree of difficulty (determined by the resident performing the case) was not significant, but unexplained is the increased injury rate with increased body mass index and increased uterine size ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of ureteral injuries following procedures such as sacrospinous fixation, vaginal vault suspensions, sacrocolpopexy, urethropexy, and bladder neck suspensions ranges from 2 to 11% [2,3]. Given the proximity of the ureter to the female genital tract, ureteral injuries are a known complication of complex pelvic reconstructive surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, no gold standard for diagnosing ureter injury is available. Although intraoperative cystoscopy [ 35 ] and postoperative CT [ 31 ] reportedly allow precise diagnosis of unsuspected ureteral injuries, it remains unclear whether these tests are able to detect varying degrees of ureteral obstruction as suggested by Siddighi [ 19 ]. In our hospital, intraoperative cystoscopy, postoperative CT and ultrasonography were not routinely performed in CRS-HIPEC, and this might also be the case in other hospitals.…”
Section: Discussionmentioning
confidence: 99%